Mapping of Nursing Interventions in Heart Failure Management: Research Trends, Collaboration Networks, and Future Research Opportunities - Acep Hidayatul Mustopa; IIm Imas Masru’ah (Universitas Galuh, 2026)
Introduction: Heart failure is a cardiovascular disease with high morbidity and mortality rates, necessitating effective nursing interventions. Although the number of publications on nursing interventions continues to increase, bibliometric studies that map research trends remain limited. Objective: This study aims to analyze research trends, author collaboration patterns, conceptual structures, and research opportunities regarding nursing interventions in heart failure management. Methods: This bibliometric study used publication data from the Scopus and Dimensions databases for the period 2005–2026. A total of 4,081 publications were identified, and after the screening process, 287 articles involving 1,706 authors were selected. The analysis was conducted using VOSviewer version 1.6.21 through co-occurrence and co-authorship mapping, with a minimum threshold of two documents per author. Results: The co-occurrence analysis yielded four clusters dominated by the keywords “treatment,” “congestive heart failure,” “effect,” and “self-care.” The density analysis indicated that the topics of telehealth, artificial intelligence, mobile health, and remote patient monitoring still have low research density. The co-authorship analysis identified 287 authors forming 28 collaboration clusters, indicating that research collaboration networks remain relatively fragmented. Conclusion: Research is still dominated by evaluations of conventional interventions. Future research should strengthen multidisciplinary collaboration and develop digital technology-based nursing interventions to improve the quality of care for patients with heart failure